1979
DOI: 10.1161/01.cir.59.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Cellular electrophysiology of human myocardial infarction. 1. Abnormalities of cellular activation.

Abstract: SUMMARY Ventricular tissues were obtained at the time of operation from 12 patients who underwent aneurysmectomy or mitral valve replacement. The electrophysiologic characteristics of these tissues were determined in a tissue bath using microelectrodes. Normal-appearing action potentials were recorded from surviving Purkinje fibers and ventricular muscle cells within infarcted ventricular tissues. Normal muscle action potential recordings from infarcted tissues were similar to action potentials from noninfarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Note that the VPC, and VPC, intervals gradually shorten as the driving cycle length (CL) progressively decreases. fast sodium channel rather than the calcium-dependent slow channel response (45,46) in our group I patients.…”
Section: Discussionmentioning
confidence: 57%
“…Note that the VPC, and VPC, intervals gradually shorten as the driving cycle length (CL) progressively decreases. fast sodium channel rather than the calcium-dependent slow channel response (45,46) in our group I patients.…”
Section: Discussionmentioning
confidence: 57%
“…The effects of verapamil and diltiazem on the mechanical alternans are summarized in figure 6. Verapamil attenuated the 34 We have previously shown that the STA is a correlative to the alternation in phase 2 of a membrane action potential, and that STA is not always accompanied by the alternation of the duration of the action potential.5 Therefore, it seems that the alternation in the calcium flow during the phase 2 may be involved in STA. In this study, verapamil and diltiazem prominently attenuated the degree of STA.…”
Section: Resultsmentioning
confidence: 93%
“…The loss of cells and cell-to-cell connection that occurs in chronic infarction has been associated with both generalized and local abnormalities of activation in other preparations.20 22 The changes in P layer activation noted in the present study, specifically generalized slowing, local conduction block, and fragmentation as well as electrotonic distortion of action potentials, are strikingly similar qualitatively to abnormalities noted in canine epicardial muscle overlying a chronic infarction20-22 and in isolated human tissue. 23,[36][37][38] It seems clear from our late studies of P and VM activation that the P layer in ischemic regions remains quite viable electrophysiologically, despite complete loss of the underlying VM layer. Despite rather modest generalized slowing, 1:1 conduction was routinely maintained even to sites deep within the ischemic zone.…”
Section: Discussionmentioning
confidence: 99%